Impact of protocol‐based physiotherapy on insulin sensitivity and peripheral glucose metabolism in critically ill patients. Issue 2 (24th January 2022) - Carbon, Niklas M.; Engelhardt, Lilian J.; Wollersheim, Tobias; Grunow, Julius J.; Spies, Claudia D.; Märdian, Sven; Mai, Knut; Spranger, Joachim; Weber‐Carstens, Steffen
Abstract: Background: The impact of physiotherapy on insulin sensitivity and peripheral glucose metabolism in critically ill patients is not well understood. Methods: This pooled analysis investigates the impact of different physiotherapeutic strategies on insulin sensitivity in critically ill patients. We pooled data from two previous trials in adult patients with sequential organ failure assessment score (SOFA)≥ 9 within 72 h of intensive care unit (ICU) admission, who received hyperinsulinaemic euglycaemic (HE) clamps. Patients were divided into three groups: standard physiotherapy (sPT, n  = 22), protocol‐based physiotherapy (pPT, n  = 8), and pPT with added muscle activating measures (pPT+, n  = 20). Insulin sensitivity index (ISI) was determined by HE clamp. Muscle metabolites lactate, pyruvate, and glycerol were measured in the M. vastus lateralis via microdialysis during the HE clamp. Histochemical visualization of glucose transporter‐4 (GLUT4) translocation was performed in surgically extracted muscle biopsies. All data are reported as median (25th/75th percentile) (trial registry: ISRCTN77569430 and ISRCTN19392591/ethics approval: Charité‐EA2/061/06 and Charité‐EA2/041/10). Results: Fifty critically ill patients (admission SOFA 13) showed markedly decreased ISIs on Day 17 (interquartile range) 0.029 (0.022/0.048) (mg/min/kg)/(mU/L) compared with healthy controls 0.103 (0.087/0.111), P  < 0.001. ISI correlated with muscle strength measured by medical research council (MRC) score at first awakening ( r  = 0.383, P  = 0.026) and at ICU discharge ( r  = 0.503, P  = 0.002). Different physiotherapeutic strategies showed no effect on the ISI [sPT 0.029 (0.019/0.053) (mg/min/kg)/(mU/L) vs. pPT 0.026 (0.023/0.041) (mg/min/kg)/(mU/L) vs. pPT+ 0.029 (0.023/0.042) (mg/min/kg)/(mU/L); P  = 0.919]. Regardless of the physiotherapeutic strategy metabolic flexibility was reduced. Relative change of lactate/pyruvate ratio during HE clamp is as follows: sPT 0.09 (−0.13/0.27) vs. pPT 0.07 (−0.16/0.31) vs. pPT+ −0.06 (−0.19/0.16), P  = 0.729, and relative change of glycerol concentration: sPT −0.39 (−0.8/−0.12) vs. pPT −0.21 (−0.33/0.07) vs. pPT+ −0.21 (−0.44/−0.03), P  = 0.257. The majority of ICU patients showed abnormal localization of GLUT4 with membranous GLUT4 distribution in 37.5% (3 of 8) of ICU patients receiving sPT, in 42.9% (3 of 7) of ICU patients receiving pPT, and in 53.8% (7 of 13) of ICU patients receiving pPT+ (no statistical testing possible). Conclusions: Our data suggest that a higher duration of muscle activating measures had no impact on insulin sensitivity or metabolic flexibility in critically ill patients with sepsis‐related multiple organ failure.